THE ANALYSIS OF VERBAL INTERACTION BETWEEN TEACHER AND STUDENTS IN THE CLASSROOM - Huraerah, Nike Rosmeisarah (2013)
The study entitled The Analysis of Verbal Interaction between Teacher and Students in the Classroom aims at investigating the realization of verbal interaction between the teacher and the students in the classroom and the way the teacher gets response from the students. The study employed a qualitative research design. It was conducted at one of the state senior high schools in Bandung. The subjects were an English teacher and 40 students of an English class. The data were collected through videotaping and interview. The data were analyzed by applying Flander's Interaction Analysis Categories (FIAC) focusing on types of teacher talk and student talk. The findings indicate that the teacher acted as the most dominant interlocutor during teaching and learning process. The result also found that all of the teacher talk categories of FIAC were revealed in this study which covered, beginning from the highest percentage to the lowest one: asking questions, giving direction, criticizing, accepting ideas, lecturing, accepting feeling and praising. In terms of student talk, student's response and initiation were revealed in this study. The teacher conducted indirect teaching more rather than direct one. In addition, the teacher mostly adopted a role as the controller and initiator in the classroom in regard with the teacher frequently led the flow of interaction. It was also found that students' responses played a significant part in the classroom interaction. Mostly, students' responses were obtained by asking questions, giving directions and criticizing. Therefore, this study suggested teacher to improve student's verbal participation and the target language to interact in classroom. Keywords: Classroom, Interaction, Verbal Classroom Interaction, Teacher Talk, Student Talk, Student's Response Penelitian ini berjudul "The Analysis of Verbal Interaction between Teacher and Students in the Classroom yang bertujuan meneliti interaksi verbal antara guru dan siswa di kelas dan meneliti cara guru mendapatkan tanggapan dari siswa. Penelitian ini bersifat kualitatif. Dilaksanakan di salah satu Secular Menengah Atas di Bandung. Subjek dari penelitian ini terdiri dari seorang guru dan 40 siswa pada mata pelajaran Bahasa Inggris. Data didapatkan melalui wawancara dan juga rekaman video. Yang selanjutnya di analisis dengan menggunakan Flander's Interaction Analysis Categories (FIAC) yang fokus pada jenis pembicaraan guru dan siswa. Hasil penelitian menyatakan bahwa guru berperan sebagai sosok yang paling dominan berbicara ketika proses belajar mengajar berlangsung. Ditemukan juga bahwa beberapa jenis pembicaraan guru yang sebagaimana tercantum dalam kategori FIAC, dimulai dari jumlah persentase tertinggi yaitu, memberikan pertanyaan, memberikan arahan, megkritisi, menerima masukan, menerima perasaan/tingkah laku siswa dan member pujian. Dalam kategori jenis pembicaraan siswa, member tanggapan dan berinisiasi juga ditemukan dalam penelitian ini. Guru lebih sering menggunakan teknik pengajaran tidak langsung dibandingkan pengajaran secara langsung. Selain itu, di dalam kelas, guru cenderung berperan sebagai pengontrol dan juga perakarsa atau bisa disebut juga pengambil inisiatip., dalam hal ini mengatur berjalannya proses interaksi di dalam kelas. Dari data juga diperoleh bahwa tanggapan siswa berperan signifikan did lam interaksi kelas. Tanggapan siswa palin tinggi dihasilkan melalui hasil proses guru bertanya, memberikan arahan dan juga memberikan kritik. Dengan demikian, penelitian ini menyarankan kepada guru untuk meningkatkan partisipasi verbal siswa dan bahasa target untuk berinteraksi di dalam kelas. Kata Kunci: Kelas, Interaksi, Interaksi Kelas Secara Verbal , Pembicaraan Guru, Pembicaraan Siswa, Tanggapan Siswa